Analisis Kemampuan Serapan CO2 dan Simpanan Karbon Pada Hutan Mangrove Di Desa Parida Kecamatan Lasalepa Kabupaten Muna - La Ode Siwi; Basrudin Basrudin; Aminuddin Mane Kandari; Kahirun Kahirun; Herlan Hidayat; Mohammad Irsan (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2022)
This study aims to determine the potential for CO2 uptake and carbon storage on the mangrove forest of Parida Village Lasalepa District Muna Regency. This research was conducted in January 2022 at Parida Village, Lasalepa District, Muna Regency. The sampling in this study used the purposive sampling method, the determination of the sampling was selected systematically with an intensity of 1%. The placement of the measuring plots is based on the zoning of the mangrove forest which is made of 3 (three) plots, where each plot is 15 m x 15 m (225 m2). The variables in this study were the diameter of an adult's chest height to determine above-ground biomass and carbon (above ground) without cutting down trees (non-destructive). Biomass is determined by Allometric equations. The carbon is determined by of the biomass. The results showed that the potential for CO2 absorption and carbon storage in mangroves in Parida Village, Lasalepa District, Muna Regency had an average CO2 absorption of 1057,49 ton.ha-1, and carbon storage 288,41 ton.ha-1. The carbon value is influenced by environmental conditions, the type of wood mass, the diameter of the mangrove trunk and the number of species contained in a plot.Keywords: Mangrove Forest, CO2Absorption,Carbon Storage. AbstrakPenelitian ini bertujuan untuk mengetahui potensi serapan CO2 dan simpanan karbon pada hutan mangrove di Desa Parida Kecamatan Lasalepa Kabupaten Muna.Penelitian ini dilaksanakan pada Bulan Januari 2022 bertempat di Desa Parida Kecamatan Lasalepa Kabupaten Muna.Adapun pengambilan sampel dalam penelitian ini menggunakan metode purposive sampling, penentuan pengambilan sampel dipilihsecara sistematis dengan intensitas 1%. Penempatan plot ukur didasarkan pada zonasi hutan mangrove yang dibuat 3 (tiga) plot, dimana masing-masing plot berukuran 15 m x 15 m (225 m2). Variabel dalam penelitian ini yaitu diameter batang untuk menentukan bioamassa dan jumlah karbon diatas permukaan tanah (above ground) dengan tanpa menebang pohon (non destuktif).Biomassa ditentukan dengan persamaan Allometrik.Adapun karbon ditentukan dengan ½ dari biomassa. Hasil penelitian menunjukan bahwa potensi serapan CO2 dan simpanan karbon pada hutan mangrove di Desa Parida Kecamatan Lasalepa Kabupaten Muna memiliki rata-rata serapan CO2 sebesar 1057,49ton.ha-1, serta simpanankarbon 288,41 ton.ha-1. Besar nilai karbon dipengaruhi oleh kondisi lingkungan, jenis masa kayu, diameter batang mangrove dan jumlah jenis yang terdapat dalam suatu plot.Kata Kunci : Hutan Mangrove, Serapan CO2, Simpanan Karbon